2022
DOI: 10.3389/fphys.2022.913457
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-Structure Interaction Simulations of Repaired Type A Aortic Dissection: a Comprehensive Comparison With Rigid Wall Models

Abstract: This study aimed to evaluate the effect of aortic wall compliance on intraluminal hemodynamics within surgically repaired type A aortic dissection (TAAD). Fully coupled two-way fluid-structure interaction (FSI) simulations were performed on two patient-specific post-surgery TAAD models reconstructed from computed tomography angiography images. Our FSI model incorporated prestress and different material properties for the aorta and graft. Computational results, including velocity, wall shear stress (WSS) and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…Compared with compliant simulations, the assumption of a rigid wall in TBAD has been shown to reduce peak TAWSS, expand regions of high oscillatory shear and low TAWSS, and affect the distribution of flow through luminal tears. 4 , 41 However, the magnitude of these differences increased with flap compliance which is likely to be low due to the chronicity of this case of TBAD. Furthermore, time shifts in TL and FL pressure waves tend to zero in cases where large or numerous luminal communications are present; the assumption of a rigid flap has been previously justified on this basis.…”
Section: Discussionmentioning
confidence: 92%
“…Compared with compliant simulations, the assumption of a rigid wall in TBAD has been shown to reduce peak TAWSS, expand regions of high oscillatory shear and low TAWSS, and affect the distribution of flow through luminal tears. 4 , 41 However, the magnitude of these differences increased with flap compliance which is likely to be low due to the chronicity of this case of TBAD. Furthermore, time shifts in TL and FL pressure waves tend to zero in cases where large or numerous luminal communications are present; the assumption of a rigid flap has been previously justified on this basis.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, time shifts in TL and FL pressure waves tend to zero in cases where large or numerous luminal communications are present; the assumption of a rigid flap has been previously justified on this basis 6 . Even where flap compliance is large, TMP is minimally affected 4,37 . Finally, we have used a RANS turbulence model for computational efficiency which may affect the accuracy of WSS indices, however this is not yet well-documented 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In terms of modelling assumptions, walls were assumed to be rigid. Compared with compliant simulations, the assumption of a rigid wall in TBAD has been shown to reduce peak TAWSS, expand regions of high oscillatory shear and low TAWSS, and affect the distribution of flow through luminal tears 37,4 . However, the magnitude of these differences increased with flap compliance which is likely to be low due to the chronicity of this case of TBAD.…”
Section: Discussionmentioning
confidence: 99%
“…The role of hemodynamics in aortic dissection formation is well-recognized in the literature. Authors [12,25,26] have shown the existence of preferential sites for aortic dissection formation and have found that low and oscillating parietal stress favors dissection development by its impact on the shape and structure of endothelial cells. The improvement of medical imaging techniques [27][28][29][30][31] allow for providing more precise information on the rheological behavior of blood.…”
Section: Hemodynamical Fl Owmentioning
confidence: 99%
“…It is necessary to igure out the mechanical behavior of the aortic wall and the patient's hemodynamic characteristics to build a realistic bio-faithful model. Many researchers [12][13][14] have been interested in numerical simulations of hemodynamics for several years, allowing the location of dissections to be correlated with the area of regions where blood low is disturbed.…”
Section: Introductionmentioning
confidence: 99%